2003
DOI: 10.1213/01.ane.0000061583.77068.0b
|View full text |Cite
|
Sign up to set email alerts
|

Diluent Volume for Epidural Fentanyl and Its Effect on Analgesia in Early Labor

Abstract: In early laboring patients, the volume in which 100 micro g of epidural fentanyl (after a lidocaine-epinephrine test dose) is administered does not affect the onset or duration of ambulatory analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
3
7
0
Order By: Relevance
“…However, all the patients in Cohen's study [20] received an initial 12-ml epidural bolus of bupivacaine (0.0625% or 0.125%) in addition to the lidocaine-epinephrine test dose, while the patients in Calimaran's study [21] received a lidocaineepinephrine epidural test dose after having received 2.5 mg intrathecal bupivacaine. Our use of epidural opioid after a test dose, without the use of adjuvant local anesthetic, does not result in signifi cant motor block [1][2][3]. One patient in the current study, and two patients in our previous studies [2,3], complained of numbness; these symptoms were presumably due to the local anesthetic in the test dose and the bupivacaine in the infusion.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…However, all the patients in Cohen's study [20] received an initial 12-ml epidural bolus of bupivacaine (0.0625% or 0.125%) in addition to the lidocaine-epinephrine test dose, while the patients in Calimaran's study [21] received a lidocaineepinephrine epidural test dose after having received 2.5 mg intrathecal bupivacaine. Our use of epidural opioid after a test dose, without the use of adjuvant local anesthetic, does not result in signifi cant motor block [1][2][3]. One patient in the current study, and two patients in our previous studies [2,3], complained of numbness; these symptoms were presumably due to the local anesthetic in the test dose and the bupivacaine in the infusion.…”
Section: Discussionsupporting
confidence: 41%
“…Our use of epidural opioid after a test dose, without the use of adjuvant local anesthetic, does not result in signifi cant motor block [1][2][3]. One patient in the current study, and two patients in our previous studies [2,3], complained of numbness; these symptoms were presumably due to the local anesthetic in the test dose and the bupivacaine in the infusion. Epidural 0.1% bupivacaine with sufentanil, as part of a PCEA technique, results in detectable motor block in approximately 20% of patients [22].…”
Section: Discussionsupporting
confidence: 41%
“…Local anesthetics, such as lidocaine, have been used for this purpose; however, some disadvantages accompany epidural anesthesia with lidocaine, such as short duration of action and its effects on the neonatal Apgar score (1). Studies have examined whether adding various drugs to the epidural solution can decrease these unwanted effects (2)(3)(4)(5)(6). Among these, opioids have widely been used in various methods of epidural anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…The value of opioids in labor analgesia has been further investigated. Connelly et al 181 observed in 60 laboring primigravidae that dilution of fentanyl 100 lg to volumes of 2, 10 and 20 mL with a 3 mL epidural test dose of 1.5% lidocaine + 1:200 000 epinephrine, did not affect the onset or duration of block or the ability to ambulate.…”
Section: Analgesia For Labor and Deliverymentioning
confidence: 99%